2021
DOI: 10.3390/biom11060910
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Survival within and around the Hematoma: Quantification by MRI in Patients with Intracerebral Hemorrhage

Abstract: White matter (WM) injury and survival after intracerebral hemorrhage (ICH) has received insufficient attention. WM disruption surrounding the hematoma has been documented in animal models with histology, but rarely in human ICH with noninvasive means, like magnetic resonance imaging (MRI). A few human MRI studies have investigated changes in long WM tracts after ICH remote from the hematoma, like the corticospinal tract, but have not attempted to obtain an unbiased quantification of WM changes within and aroun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…To avoid such secondary injuries, several minimally-invasive procedures have subsequently been developed, with encouraging results ( 4 , 8 , 9 ). Recently, the critical view on surgical interventions has been reinforced by evidence of surviving white matter fibers within the hematoma that could be damaged by surgical interventions, which in turn may negatively impact self repair mechanisms and thereby functional outcome ( 22 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To avoid such secondary injuries, several minimally-invasive procedures have subsequently been developed, with encouraging results ( 4 , 8 , 9 ). Recently, the critical view on surgical interventions has been reinforced by evidence of surviving white matter fibers within the hematoma that could be damaged by surgical interventions, which in turn may negatively impact self repair mechanisms and thereby functional outcome ( 22 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Surely, the technique is open for further improvement, for example a more specific and elaborated planning of the trajectory by using DTI to determine – and thereby sparing –the white matter tracts [as, e.g., reported by Du et al, Steineke and Barbery and Zhang et al ( 44 46 )] and also predict clinical outcome ( 47 , 48 ). Additionally, the supplement of tractography could be used to further evaluate the presence and role of surviving white matter tracts within the hematoma that are thought to be at risk for damage by the surgical intervention ( 22 , 23 ). However, the time delay to be expected as a result of performing tractography [median time to surgery reported by Zhang et al: 21 h ( 46 )] should not be lost sight of, since the recently reported more pronounced benefit of hematoma evacuation when MIS was performed earlier ( 11 ).…”
Section: Discussionmentioning
confidence: 99%